Learning Docker : optimize the power of Docker to run your applications quickly and easily - Raj, Pethuru; Chelladhurai, Jeeva S.; Singh, Vinod (Community experience distilled., 2015)
Chapter 6: Running Services in a Container; A brief overview of container networking; Envisaging the Container as a Service; Building an HTTP server image; Running the HTTP server Image as a Service; Connecting to the HTTP service; Exposing container services; Publishing container ports - the -p option; Network Address Translation for containers; Retrieving the container port; Binding a container to a specific IP address; Auto-generating the Docker host port; Port binding using EXPOSE and the -P option; Summary; Chapter 7: Sharing Data with Containers; The data volume